EFEKTIFITAS MEDIA VIDEO UNTUK MENINGKATKAN KETERAMPILAN MEMPERBAIKI SEPEDA MOTOR PADA ANAK GANGGUAN PENDENGARAN di SLB YPPLB PADANG - FASTA BIQUL KHAIRAT (Jurnal Penelitian Pendidikan Khusus, 2015)
This research was based on field observation from initial study in SLB YPPLB Padang where researcher saw an interesting subject which was student were not gave enough attention while automotive subject course went on. It was observed from student’s irresponsiveness while teacher alternately ask students performed sparkplug-clearance. The type of this research was Single Subject Research (SSR). Experiment was a treatment conducted to investigate behaviors or symptoms that occurred in a given situation. While SSR was research that used a single subject.Research finding shows that motorcycle reparation skill on sparkplug-clearance for hearing impairment child in situation A has data stability tendency of 0% able, hesitant 75%, helpable 75% and unable 25%; data stability tendency in motorcycle reparation skill on sparkplug-clearance is stable. In situation B has data stability tendency of 62.5% able, hesitant 100%, helpable 25% and unable 12.5%; therefore, data stability tendency in motorcycle reparation skill on sparkplug-clearance is stable. It can be concluded that motorcycle reparation skill on sparkplug-clearance for hearing impairment child has diverse skill when before intervention, on intervention and after intervention. Keyword: media video, keterampilan menservis, busi clearance, gangguan pendengaran.